2020
DOI: 10.35912/amor.v1i1.289
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Covid-19 on the economy of Bangka-Belitung and the performance of MSME and its impact on competitive strategies in the new normal era

Abstract: Purpose: The economy in the MSME sector is experiencing a great crisis in the face of the Covid-19 pandemic. MSME actors must change strategies to adapt to the current pandemic conditions. The purpose of this study was to examine the effects of Covid 19 on the economy and performance of MSMEs as well as the strategies adopted by MSME players in Bangka Belitung Province. Research methodology: The data collection method employed probability sampling with google form media analyzed by using cross tabulation, tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 4 publications
4
4
0
1
Order By: Relevance
“…, 2020). The findings are consistent with previous studies (Das and Kundu, 2020; Reniati et al. , 2020; Liguori and Pittz, 2020; Mardi and Siregar, 2021; Dash and Chakraborty, 2021; Panjaitan et al.…”
Section: Discussion and Findingssupporting
confidence: 94%
See 1 more Smart Citation
“…, 2020). The findings are consistent with previous studies (Das and Kundu, 2020; Reniati et al. , 2020; Liguori and Pittz, 2020; Mardi and Siregar, 2021; Dash and Chakraborty, 2021; Panjaitan et al.…”
Section: Discussion and Findingssupporting
confidence: 94%
“…With the advent of the Internet, entrepreneurs should not only identify new customers and opportunities but also develop new business models to survive as well as to thrive in their businesses (Liguori and Pittz, 2020). To survive the pandemic and grow in the future, entrepreneurs opted for an online selling strategy and maintenance of customer databases (Reniati et al, 2020). The findings are consistent with previous studies (Das and Kundu, 2020;Reniati et al, 2020;Liguori and Pittz, 2020;Mardi and Siregar, 2021;Dash and Chakraborty, 2021;Panjaitan et al, 2021).…”
Section: Discussion and Findingssupporting
confidence: 82%
“…The three levy reception posts with the lowest growth had negative growth values, meaning that the trend decreased between 2016 and 2020 due to the Covid-19 outbreak. These results are in line with the research results (Reniati et al, 2019).…”
Section: Growth Analysissupporting
confidence: 93%
“…Another qualitative study examining the impact of COVID-19 on MSMEs reported a decrease in the turnover of MSMEs actors during the pandemic (Amri, 2020). Similarly, the study by Reniati et al (2019) reported that the turnover of the MSMEs in Bangka Belitung was below 10 million, which was lower than before the pandemic. Another qualitative research that examined MSMEs found that the threat of COVID-19 affected the income decrease of MSMEs (Akpan et al, 2020;Andika et al, 2020;Fathoni, 2019;Sarmigi, 2020;Soehardi et al, 2020).…”
Section: Introductionmentioning
confidence: 88%